Chronic lymphocytic lymphoma and concomitant renal cell carcinoma (Clear Cell Type): Review of the literature - Uz, Burak; Dolasik, Ilhan; Ucer, Ozlem; Dagli, Adile Ferda; Simsek, Sercan (Elsevier Ltd, 2016)
In the present report, a 73 years-old male patient who developed clear cell type renal cell carcinoma (RCC) 5 years after the diagnosis of chronic lymphocytic lymphoma (CLL) and plausible explanations for this association were discussed by the authors. The incidence of CLL and RCC occurring in the same patient is higher than that expected in the general population. Various explicative hypotheses of this concurrence include treatment-related development of a second malignancy, immunomodulatory mechanisms, viral aetiology, cytokine (interleukin 6) release from a tumor, and common genetic mutations. Further investigations are warranted. © 2016 The Authors.
Keywords: Chronic lymphocytic lymphoma; Renal cell carcinoma